Acoustic Characterization of Axial Flow Left Ventricular Assist Device Operation In Vitro and In Vivo. Issue 1 (January 2016) - Yost, Gardner L.; Royston, Thomas J.; Bhat, Geetha; Tatooles, Antone J.
Abstract : The use of left ventricular assist devices (LVADs), implantable pumps used to supplement cardiac output, has become an increasingly common and effective treatment for advanced heart failure. Although modern continuous-flow LVADs improve quality of life and survival more than medical management of heart failure, device malfunction remains a common concern. Improved noninvasive methods for assessment of LVAD function are needed to detect device complications. An electronic stethoscope was used to record sounds from the HeartMate II axial flow pump in vitro and in vivo . The data were then uploaded to a computer and analyzed using two types of acoustic analysis software. Left ventricular assist device acoustics were quantified and were related to pump speed, acoustic environment, and inflow and outflow graft patency. Peak frequency values measured in vivo were found to correlate strongly with both predicted values and in vitro measurements ( r > 0.999). Plots of the area under the acoustic spectrum curve, obtained by integrating over 50 Hz increments, showed strong correlations between in vivo and in vitro measurements ( r > 0.966). Device thrombosis was found to be associated with reduced LVAD acoustic amplitude in two patients who underwent surgical device exchange.